Prevalence of iron deficiency anaemia and risk factors in 1,010 adolescent girls from rural Maharashtra, India: a cross-sectional survey - Ahankari, Anand S.; Myles, Puja R.; Fogarty, Andrew W.; Dixit, J.V.; Tata, Laila J. (Elsevier, 2017)
Objective: Iron deficiency anaemia (IDA) is the most common nutritional disorder observed in adolescent girls in India. Our aim was to investigate the prevalence and risk factors associated with IDA in rural Maharashtra, India to address current evidence gaps.